Тираны: роман / Ю. В. Остапенко ; автор идеи К. Рыков - Остапенко Юлия Владимировна (Этногенез, 2012)
Экземпляры: аб. ЦБ (2017.14.12) / Инвентарный номер: 3672 / Цена: / Сис.шифр: 84Р6 / Авт.знак: О-76 / ББК: 84(2Рос=Рус)6-45